2005
DOI: 10.1111/j.1440-1630.2005.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Australian and New Zealand indigenous people's spirituality and mental health

Abstract: Background: Spirituality has been defined as an overarching construct that involves personal beliefs or values that provide a sense of meaning and unity with self, people, nature and universe. Spirituality may be experienced within or outside formal religion. At least in English-speaking countries, therapists reported discussing spiritual issues with service users more frequently than before. In the literature, there continues to be debate regarding definitions of spirituality and how spirituality fits with oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 49 publications
1
33
0
1
Order By: Relevance
“…The discrepancies also occurred when the therapist expected the clients to be able to do things and be effective and productive while the clients wanted to find meaning through spiritual activities. This confirms the work of other researchers, suggesting that spirituality plays a significant role in the lives of the client as well as in the client's personal functioning and overall health and well-being in the performance of everyday occupation (42,43,45). In fact, spirituality and religion play important roles in the collective belonging and group identity of many people with a Middle Eastern background.…”
Section: Discussionsupporting
confidence: 87%
“…The discrepancies also occurred when the therapist expected the clients to be able to do things and be effective and productive while the clients wanted to find meaning through spiritual activities. This confirms the work of other researchers, suggesting that spirituality plays a significant role in the lives of the client as well as in the client's personal functioning and overall health and well-being in the performance of everyday occupation (42,43,45). In fact, spirituality and religion play important roles in the collective belonging and group identity of many people with a Middle Eastern background.…”
Section: Discussionsupporting
confidence: 87%
“…Allen and Lo also indicated that the higher levels of religious devotion were related to the reduced possibility for drug abuse (20). Tse et al argue that spirituality makes the life of individuals meaningful and provides a source of resistance for them under life difficult conditions (21). Spirituality may improve internal power and enable the individuals to find the concept under stressful conditions and to create optimistic attitude and positive objective in life and subsequently reduced anxiety in life for persons (22).…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous spirituality can encompass a range of dimensions, including the values of reciprocity, mutual respect, regard for planet earth and all creation as relatives (kin), traditional cosmologies and philosophies, the cultural ethos upon which individual and group identities unfold, and sustainable consumption practices that involve stewardship for all living things (Indigenous Peoples Summit 2008). In terms of a definition, spirituality incorporates an overarching construct involving beliefs and values that provide a sense of meaning, purpose, connectivity, and unity with respect to peoples notions of self, community, nature and the universe (Tse et al 2005). In that its not always formally expressed in doctrine or compartmentalized from everyday life, an indigenous world view of spirituality often entails a unity of body, mind, and spirit, within the context of Something greater that sustains and guides.…”
Section: Indigenous Spiritualitymentioning
confidence: 99%